Cenários de mudanças climáticas e impacto no zoneamento agroclimático de espécies florestais no Estado do Espírito Santo - Pirovani, Daiani Bernardo (2014)
This work objective to evaluate the impact of climate change on suitable to the cultivation of teak forest species, peach palm, Neem Indian, Australian cedar, Pinus elliottii, Pinus caribaea, Pinus taeda and Pinus oocarpa in the state of Espírito Santo (E